Staphylococcus aureus coagulases are exploitable yet stable public goods in clinically relevant conditions - Trivedi, Urvish; Madsen, Jonas S.; Everett, Jake; Fell, Cody; Russel, Jakob; Haaber, Jakob; Crosby, Heidi A.; Horswill, Alexander R.; Burmølle, Mette; Rumbaugh, Kendra P.; Sørensen, Søren J. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Coagulation is an innate defense mechanism intended to limit blood loss and trap invading pathogens during infection. However, Staphylococcus aureus has the ability to hijack the coagulation cascade and generate clots via secretion of coagulases. Although many S. aureus have this characteristic, some do not. The population dynamics regarding this defining trait have yet to be explored. We report here that coagulases are public goods that confer protection against antimicrobials and immune factors within a local population or community, thus promoting growth and virulence. By utilizing variants of a methicillin-resistant S. aureus we infer that the secretion of coagulases is a cooperative trait, which is subject to exploitation by invading mutants that do not produce the public goods themselves. However, overexploitation, “tragedy of the commons,” does not occur at clinically relevant conditions. Our micrographs indicate this is due to spatial segregation and population viscosity. These findings emphasize the critical role of coagulases in a social evolution context and provide a possible explanation as to why the secretion of these public goods is maintained in mixed S. aureus communities.